2000
DOI: 10.1002/(sici)1098-2795(200006)56:2<163::aid-mrd7>3.3.co;2-v
|View full text |Cite
|
Sign up to set email alerts
|

Oocyte metabolism predicts the development of cat embryos to blastocyst in vitro

Abstract: Current methods for detecting complete oocyte maturation and developmental competence are inadequate. The objectives of this study were to (1) examine the relationship between cat oocyte energy metabolism and development in vitro after fertilization and (2) determine if cumulus cell metabolism could be used to predict development of individual oocytes after fertilization in vitro. The hanging drop method was used to assess metabolism of three different types of cat oocytes: immature (IMO), in vitro matured (IV… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
77
1
1

Year Published

2005
2005
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(90 citation statements)
references
References 0 publications
11
77
1
1
Order By: Relevance
“…Higher rates of glycolysis by bovine oocytes denuded at the end of a 24-h maturation period were associated with increased developmental potential (Krisher & Bavister 1999). Blastocyst development in cats was also associated with higher rates of glycolysis by denuded oocytes; however, no correlation was determined between glycolytic activity or glucose oxidation by cumulus cells and subsequent oocyte development (Spindler et al 2000). In the present study, COCs that were able to fertilize consumed more glucose and produced more lactate than the oocytes that failed to fertilize.…”
Section: Discussioncontrasting
confidence: 51%
“…Higher rates of glycolysis by bovine oocytes denuded at the end of a 24-h maturation period were associated with increased developmental potential (Krisher & Bavister 1999). Blastocyst development in cats was also associated with higher rates of glycolysis by denuded oocytes; however, no correlation was determined between glycolytic activity or glucose oxidation by cumulus cells and subsequent oocyte development (Spindler et al 2000). In the present study, COCs that were able to fertilize consumed more glucose and produced more lactate than the oocytes that failed to fertilize.…”
Section: Discussioncontrasting
confidence: 51%
“…However, numerous groups have demonstrated that despite the low glycolytic activity in the oocyte, there appears to be an important positive relationship between this relatively low glycolytic activity and developmental competence of oocytes (Krisher & Bavister 1999, Spindler et al 2000, Durkin et al 2001, Herrick et al 2006. For example, oocytes derived from pre-pubertal cattle and sheep (which have lower developmental competence) have delayed increases in glycolytic activity during maturation compared to oocytes derived from adult animals (higher developmental competence), with the rate of glucose metabolism in adult oocytes constantly increasing over a 24-h period, compared to increases in activity at the end of maturation in prepubertal derived oocytes (O'Brien et al 1996, Steeves & Gardner 1999.…”
Section: Glycolysismentioning
confidence: 99%
“…Recently, we have demonstrated that the quality of cat embryos can be predicted from the metabolic pattern of the source oocytes [53] as in cattle [54]. Metabolic selection of individual companion embryos is labor intensive and may not be available at the site of gamete rescue.…”
Section: Introductionmentioning
confidence: 99%
“…Metabolic selection of individual companion embryos is labor intensive and may not be available at the site of gamete rescue. As oocyte metabolism is linked to overall developmental potential [53,54], including time to first cleavage [55], we suggest that selection of high quality cat embryos can also be performed by assessing time to first cleavage as in cattle [56] and humans [57].…”
Section: Introductionmentioning
confidence: 99%